E-Payment Methods and E-Commerce Growth in Uganda: Evidence from Kampala - Uganda’s Central Business District - Martin Kasenge; Arthur Butime (Goodwood Publishing, 2024)
Purpose: The study assessed the effect of e-payment methods on the growth of e-commerce in Uganda, specifically focusing on the impact of e-wallets/e-cash, debit/credit cards, and money transfer services on e-commerce growth in Kampala. Research/methodology: A cross-sectional design was used with a sample of 384 participants. Data were collected through structured questionnaires, cleaned, organized, and analyzed using SPSS, employing correlation and regression models for inferential analysis. Results: The study found that e-payment methods, including debit/credit cards, money transfer services, and e-wallets/e-cash, positively and significantly associate with e-commerce growth. However, while debit/credit cards and money transfer services significantly predict e-commerce growth, e-wallets/e-cash have a positive but insignificant effect. Overall, e-payment methods account for 33.1% of the variation in e-commerce growth. Conclusions: E-payment methods, especially debit/credit cards and money transfer services, significantly contribute to e-commerce growth in Kampala. E-wallets show a positive but insignificant effect. To achieve sustainable impact, further support is needed for e-payment adoption. Limitations: The study focused on a limited range of e-payment methods, excluding others used in the sector, which affects generalizability. Additionally, only Kampala was studied, though other regions in Uganda also engage with e-payment systems. Kampala, as the central business hub, is a key area for innovations that spread to other cities. Contribution:. E-payment systems significantly predict e-commerce growth. Key e-commerce players should encourage the use of e-payments to foster trade growth, as their adoption will help stimulate e-commerce activity.